Pengaruh Executive Incentive terhadap Firm Value melalui Earning Management sebagai Variabel Intervening pada Perusahaan yang Terdaftar dalam Saham Indeks Kompas 100 di Bursa Efek Indonesia Periode 2010-2014 - Sieny Lauw; Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of executive incentive to earning management, earning management to firm value, and executive incentive to firm value. This study also examine the indirect and significant relationship of executive incentive to firm value through earning management as intervening variable. The sample of this study was 32 companies listed in Kompas 100 Index in Indonesia Stock ExchangeThis study used a quantitative approach, and the data were obtained from company’s financial statement of 2010-2014. The data then processed by using smartPLS software. This study showed that there was positive and significant relationship of executive incentive and earning management, negative and significant relationship of earning management and firm value, and negative and significant relationship of executive incentive and firm value.